17p13.1 Deletion in Small B-cell Lymphocytic Lymphomas: A Prognostic Factor and Diagnostic Approach - Andreea-Georgiana STOICA; Miruna CRISTIAN; Mariana ASCHIE; Anca-Florentina MITROI; Georgiana-Camelia COZARU; Gabriela-Izabela BALTATESCU; Madalina BOSOTEANU; Mihaela-Maria GHINEA (Documenta Haematologica)
B-cell small lymphocytic lymphoma (B-SLL) belongs to the category of indolent non-Hodgkin's lymphomas and is defined by the proliferation of mature, inert B lymphocytes and their accumulation in lymphoid structures. Although it is classified as the same entity as chronic lymphocytic leukemia (B-CLL), according to the World Health Organization and the International B-CLL Task Force [1, 2], there is little data on the management of lymphocytic lymphoma, accounting for only 10-15% of B-CLL/SLL cases [3, 4]. The aim of this study is to evaluate the presence of the 17p13.1 deletion in a series of "pure" lymphocytic lymphoma cases from 2017-2020, given that it is considered an identical entity to chronic lymphocytic leukemia. It is known that del17p13.1 provides resistance to chemotherapy and is a negative prognostic factor in B-CLL, but its routine evaluation is not routinely performed in practice as part of B-SLL diagnosis. Our findings highlight the contribution of del17p13.1 identification in patients diagnosed with B-SLL, enhancing diagnostic accuracy and treatment management efficiency, suggesting its potential as a standard diagnostic tool in clinical settings. The review aims to provide a comprehensive overview for hematologists and pathologists, encouraging the adoption of del17p13.1 identification to improve patient outcomes in the management of B-SLL.